Hubungan Nilai Try Out dengan Nilai Computer Based Test pada Ujian Kompetensi Mahasiswa Profesi Pendidikan Dokter - Firdaus Firdaus; Elda Nazriati; muhammad rofi (Fakultas Kedokteran Universitas Riau, 2020)
The try out of UKMPPD is an effort to measure student’s abilities and can provide an overview about competence that have been achieved and become one into consideration for students to optimizing their attempt and effort to graduate with good grades. The purpose of this research is to analyze the relation between try out and CBT of UKMPPD results. This type of research is a correlation analytic with cross sectional approach. The data of this study were the test score of the try out and CBT UKMPPD in 2019 which total about 105. The results of this study have a significant relationship with the p value of 0.000 (<0.05) between the try out UKMPPD value and the CBT UKMPPD value. The strength of the correlation obtained is very strong at 0.75 and the direction is positive. This shows that there is a significant relationship between the try out UKMPPD score and the CBT UKMPPD score.